Copyright Protection vs Free Movement of Goods within the Internal Market of the EU - Kocev, Ljuben (ITMO University, 2021)
The article is about identification of statistical patterns in the field of trademarks and service marks reg- istration. To identify patterns, official statistical data provided in the relevant state collections were used. The analysis of dynamic changes in the certificates and the filled applications allowed us to indicate positive conclusions about the intellectual property registration in Russia. The article also provided the hypothesis of the dependency between the number of organizations in a certain region and the number of registered trademarks and service marks. It was conclud- ed that the hypothesis put forward about the presence of a possible dependence between the number of organizations in a certain region and the number of registered trademarks and service marks was partially confirmed. There really is a pattern, that is, with an increase in the number of organizations in a certain region, the number of registered trademarks and service marks increased, but it was not possible to build a clear mathematical model of dependence.
Keywords: intellectual property rights, copyright, free movement of goods, European Union, Internal Market